Functional characterization of novel germline TP53 variants in Swedish families. Issue 3 (2nd July 2019) - Kharaziha, Pedram; Ceder, Sophia; Axell, Olga; Krall, Moritz; Fotouhi, Omid; Böhm, Stefanie; Lain, Sonia; Borg, Åke; Larsson, Catharina; Wiman, Klas G.; Tham, Emma; Bajalica‐Lagercrantz, Svetlana
Abstract: Pathogenic germline TP53 variants predispose to a wide range of early onset cancers, often recognized as the Li‐Fraumeni syndrome (LFS). They are also identified in 1% of families with hereditary breast cancer (HrBC) that do not fulfill the criteria for LFS. In this study, we present a total of 24 different TP53 variants identified in 31 Swedish families with LFS or HrBC. Ten of these variants, nine exonic and one splice, have previously not been described as germline pathogenic variants. The nine exonic variants were functionally characterized and demonstrated partial transactivation activity compared to wild‐type p53. Some show nuclear localization similar to wild‐type p53 while others possess cytoplasmic or perinuclear localization. The four frameshift variants (W91Gfs*32, L111 Wfs*12, S227 Lfs*20 and S240Kfs*25) had negligible, while F134 L and T231del had low level of p53 activity. The L111 Wfs*12 and T231del variants are also deficient for induction of apoptosis. The missense variant R110C retain p53 effects and the nonsense E349* shows at least partial transcription factor activity but has reduced ability to trigger apoptosis. This is the first functional characterization of novel germline TP53 pathogenic or likely pathogenic variants in the Swedish cohort as an attempt to understand its association with LFS and HrBC, respectively. Abstract :